EFEKTIVITAS PENGGUNAAN MEDIA PUZZLE TERHADAP HASIL BELAJAR MATEMATIKA KELAS 1 SD - Dewi Na’ima; Aries Tika Damayani; Suyoto; Niwi Sruti Handayani (STKIP Subang, 2023)
The learning outcomes of mathematics for first-grade students at SDN Muktiharjo Kidul 03 tend to be low due to teacher-centered instruction, the application of conventional teaching models, and the lack of utilization of supportive learning media. The purpose of this study is to determine the effectiveness of puzzle media on student learning outcomes, particularly in the topic of comparing sizes. This research is a quantitative study using a pre-experimental design with a one-group pretest-posttest approach. The testing steps include: 1) Normality test, and 2) Mean comparison test. The conclusion of this research is that the use of puzzle media is effective for improving student learning outcomes in mathematics for first-grade students.